2013
DOI: 10.5603/cj.2013.0022
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure variability: Epidemiological and clinical issues

Abstract: (Cardiol J 2013; 20, 2: 112-120)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 86 publications
0
7
0
1
Order By: Relevance
“…According to the IDACO (an International Database on Ambulatory BP in relation to Cardiovascular Outcome) database, a 16-mm Hg increase in the nocturnal SBP was associated with stroke events (HR 1.08 [1.01-1.16]; p < 0.001) [10]. In 1,187 essential hypertension patients followed up for 3.2 years, Krzych et al [22] found that the occurrence of adverse CV events was nearly three times higher in non-dipper patients than dipper hypertensive patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…According to the IDACO (an International Database on Ambulatory BP in relation to Cardiovascular Outcome) database, a 16-mm Hg increase in the nocturnal SBP was associated with stroke events (HR 1.08 [1.01-1.16]; p < 0.001) [10]. In 1,187 essential hypertension patients followed up for 3.2 years, Krzych et al [22] found that the occurrence of adverse CV events was nearly three times higher in non-dipper patients than dipper hypertensive patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Нині проблеми здоров'я людини та соціуму, пов'язані з підвищеним артеріальним тиском, займають лідируючу позицію як у країнах Європи, так і в Америці. Оприлюднено епідеміологічні та клінічні аспекти варіабельності артеріального тиску (Krzych and Bochek, 2013;Kozeba et al, 2015). Артеріальна гіпертензіяпричина смерті людей як похилого, так і молодого віку, незважаючи на досягнення сучасної аритмології (Stevenson, 2013).…”
Section: вступunclassified
“…[6] Non-dipper hypertensive patients manifest an increased mortality risk, cardiac and extracardiac morbidity. [7,8] Possible underlying mechanisms of non-dipper profile were explored in a multitude of studies conducted over the years, identifying clinical conditions linked to disturbances of 24-h systolic and/or diastolic BP variations. [9] Complex mechanisms originating in endocrine, renal, neural, and vascular areas are involved in the pathogenesis of arterial hypertension and its circadian variability.…”
Section: Introductionmentioning
confidence: 99%